The isothermal crystallization of poly(ether ether ketone) by two‐dimensional differential scanning calorimetry correlation mapping. Issue 4 (23rd September 2016) - Al Lafi, Abdul G.; Hay, James N.
ABSTRACT: This article reports the first application of the two‐dimensional differential scanning calorimetry correlation mapping, two‐dimensional‐DSC‐CM to analyze DSC rate–time data of PEEK. This provided evidence that the isothermal crystallization reduced rate–time curves exhibited fractional n values when analyzed by the Avrami equation. These fractional n values, which increased with temperature, were consistent with the presence of two processes, primary and secondary crystallization, with an increasing contribution of the secondary crystallization to the overall crystallinity. In contrast to the known literatures, secondary crystallization was observed to proceed at early stage of primary crystallization. The study of the effect of proton irradiation, up to a dose of 9.9 MGy, showed that the fractional n value was below 3.0, and does not appear to be temperature dependent. DSC analysis of the crystallization kinetics, combined with two‐dimensional correlation mapping proved a powerful tool for investigating irradiation damage of PEEK. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44378. Abstract :